(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2020)
This article problematizes the axes of integrality proposed by the University of the Republic (Udelar), taking as a reference the Integrate Training Space Playful Practices and artistic practices: dialogues between the inside and the outside developed in Penitentiary Unit No. 6 from Punta de Rieles. To do this, some central categories such as practice and community are approached in order to tension them at first moment from different conceptual perspectives and at a second moment by making them dialogue with the proposal developed in the Unit.